Effects of Biofertilizers on Soil Quality and Vegetative Development of Mahogany (Swietenia macrophylla) and Yaca (Artocarpus heterophyllus) in the Central Peruvian Jungle - Andrea Castro-Cárdenas; Juanita Ciriaco-Poma; Juan Z. Dávalos-Prado; Víctor Soto-Aquino (Soil Systems, 2025)
The sustainability of agricultural production and the conservation of tropical ecosystems face significant challenges due to processes such as climate change and soil degradation. This study evaluated the impacts of three biofertilizers—biol (T02), vermicompost (T03), and bokashi (T04)—on soil quality and the vegetative development of two typical plants, Mahogany (Swietenia macrophylla) and Yaca (Artocarpus heterophyllus), cultivated in the Asháninka locality in the Central Peruvian Jungle. Using a completely randomized experimental design, it was generally found that treatments T04 and, to a lesser extent, T03 improved the soil quality and consequently enhanced the vegetative development of Mahogany and Yaca. Compared with the untreated controls (T01), these biofertilizers generated less dense and more porous soils and increased the water retention, organic matter, pH, and the availability of nitrogen and phosphorus nutrients. They also promoted greater biodiversity. These qualities, in turn, stimulated the vegetative development of Mahogany and Yaca, whose leaves showed considerable content of chlorophyll A and B and total chlorophyll. Thus, T03 and especially T04 proved to be effective biofertilizers for the treatment of tropical soils, promoting efficient plant growth and development in species such as Mahogany and Yaca. These findings highlight the great potential of the biofertilizers T03 and T04 in achieving sustainable agricultural production, as well as for the conservation and improvement of tropical forests.